EXAMINING THE EFFECT OF LEADERSHIP BEHAVIOR ON WORK DISCIPLINE: A STUDY AT LOCAL WATER SUPPLY UTILITY (PDAM) IN MALANG, EAST JAVA - Umi Zunaidah; Renita Kawuryan (RADJA PUBLIKA, 2023)
Leadership behavior towards work discipline has a constant emphasis on the role of leadership behavior and on the interdependence between behavior towards tasks, relationships, employee maturity and work discipline. The concept of applied leadership pertains to the engagement of subordinates in active participation within organizational activities. Leadership holds significant meaning within environmental organizations as it serves to exert influence and allocate resources towards the attainment of objectives. Leadership is significant in environmental organizations because it provides influence and guides resources toward accomplishing objectives. The aim of this research is to provide a comprehensive description and evaluation of employees' behavior in task completion, interactions within work relationships, and their level of maturity in adhering to work discipline. This study employs a measurement tool known as the Likert Scale, which consists of response options such as